New Fresnel lens loupe for nystagmus observation suitable for use by medical staff in emergency departments - Reiko Tsunoda; Yumi Dobashi; Masao Noda; Hiroaki Fushiki (International Journal of Emergency Medicine)
Abstract Background Reduction of spontaneous nystagmus by fixation, a characteristic feature of peripheral nystagmus, is important for differentiating between peripheral and central vestibular disorders. In the emergency room, Frenzel goggles are recommended to observe spontaneous nystagmus for the differential diagnosis of acute vestibular syndrome. We developed a portable loupe with a Fresnel lens to observe nystagmus. The loupe does not require power supply and can be used under ceiling lights. The aim of this study was to quantitatively and objectively compare the abilities of the loupe and conventional Frenzel goggles to observe spontaneous nystagmus and to verify that the loupe can detect peripheral nystagmus that cannot be observed with the naked eye. Methods Visual impact susceptibility was compared between the loupe and Frenzel goggles using the slow-phase velocity of nystagmus induced by the caloric test in 15 participants. Subsequently, under lighting, the nystagmus observations under the naked eye condition and with the use of the loupe were compared. Furthermore, the visibility of nystagmus was evaluated from recorded videographic images. Results In observations of nystagmus induced by the caloric test, the visual impact of the loupe was not inferior to that of Frenzel goggles. The mean slow-phase velocity of nystagmus recorded with the loupe was significantly higher than that observed with the naked eye. Nystagmus weakened under bright lighting could be recovered by the loupe as fixation was blocked and the direction of the nystagmus could be defined. Conclusions The results showed that the loupe is helpful in observing nystagmus, which is weakly observed with the naked eye under bright light. This portable, low-cost loupe, which yields superior results, can serve as an alternative to conventional Frenzel goggles in emergency medical settings where rapid assessment is required.